Penerapan Sistem Informasi Akuntansi Pembayaran Izin Tinggal Warga Negara Asing Pada Kantor Imigrasi Kelas Iii Non TPI Banggai - Irwan Moridu; Fitriani Fitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this-study was to determine and assess the Accounting Information System for Foreigners' Stay Permit Payments at the Immigration Class III Non TPI Banggai Office in Central Sulawesi. Data collection techniques used are by conducting documentation, interviews, and observations. The analysis used in this study is a descriptive method that is by analyzing the Accounting Information System for Foreigners' Residence Permit Payment conducted at the Immigration Class III Non TPI Banggai Office. The results of this study are in the Information System for Foreigners 'Permit Payments Accounting which is a computerized process and the foreigners' permit stay payment system uses a symphony payment system or online PNBP Information System that is managed directly by the Directorate General of Budget so that the results of the stay permit payment transaction carried out by the guarantor at the office the post or bank can directly enter can directly enter the state treasury as non-tax state revenue (PNBP), in general the Accounting Information System for Paying Foreign Residents Permits at the Immigration Class III Non TPI Banggai Office in Central Sulawesi is quite good and adequate. Keywords: System, Payment, Residence Permit